Reading Tutorial Program as an Alternative Intervention to Enhance Early Reading Skills in Low Socio-Economic First Graders - Pamungkas, Arinanda; Kumara, Amitya (ANIMA Indonesian Psychological Journal, 2012)
The goal of this study was to see the effectiveness of the reading tutorial program in increasing children reading ability with low socioeconomic status. The reading tutorial program provides a variety of chances to practice and do activities in reading. This program was expected to enhance the children’s reading ability. The focuses of enhancement in the children’s reading ability were: (1) sight word acquisition and (2) reading fluency. The subjects of this research were first grade students with poor reading ability and low socioeconomic status. This research used an Untreated Control Group Design with pretest and posttest. The result of this study shows that the reading tutorial program is effective in increasing children’s reading ability in sight word acquisition (SW) and fluency in word correct per minute (WPM). Tujuan studi ini adalah melihat keefektivan program tutorial membaca dalam meningkatkan kemampuan membaca anak yang berstatus sosioekonomi lemah. Program tutorial membaca ini menyediakan berbagai kesempatan untuk mempraktikkan dan beraktivitas ketika membaca. Program ini diharapkan meningkatkan kemampuan membaca anak. Fokus peningkatan dalam kemampuan membaca adalah: (1) akuisisi kata yang terlihat dan (2) kelancaran membaca. Para subjek penelitian ini adalah siswa kelas satu dengan kemampuan membaca yang rendah dan bersatus sosioekonomi lemah. Studi ini menggunakan desain Kelompok Kendali Tanpa Perlakuan dengan pra-uji dan pasca-uji. Hasil studi ini menunjukkan bahwa program tutorial membaca ini efektif dalam meningkatkan kemampuan dan kelancaran membaca anak dalam penguasaan kata yang tampak dan kelancaran kata benar per menit.